2019
DOI: 10.1111/ijfs.14173
|View full text |Cite
|
Sign up to set email alerts
|

Correlative metabolite profiling approach to understand antioxidant and antimicrobial activities from citrus essential oils

Abstract: The objective of this study was to investigate the chemical composition of the essential oils from citrus species, as well as their antioxidant and antimicrobial activities. By gas chromatography-mass spectrometry, we identified thirty-seven metabolites and a range of unique compounds, contributing to the discrimination of the species. Different biological potentialities were detected depending on the species supported the significant effect of the genetic factor. C. aurantium and C. limon exhibited the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Results are in synchronization with the previously reports of Burt (2004) and Lamine, Rahali, Hammami, and Mliki (2019). While in another study, the resistance of Gram‐positive bacteria to the EOs was more than Gram‐negative bacteria (Gupta, Garg, Uniyal, & Kumari, 2008).…”
Section: Resultssupporting
confidence: 92%
“…Results are in synchronization with the previously reports of Burt (2004) and Lamine, Rahali, Hammami, and Mliki (2019). While in another study, the resistance of Gram‐positive bacteria to the EOs was more than Gram‐negative bacteria (Gupta, Garg, Uniyal, & Kumari, 2008).…”
Section: Resultssupporting
confidence: 92%
“…Orange peel essential oil was obtained with hydro‐distillation (Lamine, Rahali, Hammami, & Mliki, 2019). For this purpose, the flavedo of fruits (Thompson variety) was removed with a manual peeler and dried in dark room (25 ± 5°C) for 2 days and milled to a particle size less than 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, CEOs from four cultivars of Citrus namely C. aurantium, C. limon, C. reticulata, and C. sinensis were tested against Candida albicans and Aspergillus flavus using disc diffusion assay. It was found that antifungal activity was highest, with EO of C. reticulata where inhibition zone (IZ) was 26.1 ± 1.20 mm and MIC of 1 mg/mL for C. albicans, while IZ of 43.1 ± 1.67 mm and MIC of 0.25 mg/mL for A. flavus [131].…”
Section: Ceo As An Antifungal Agentmentioning
confidence: 99%